Three new cases of terminal deletion of the long arm of chromosome 7 and literature review to correlate genotype and phenotype manifestations. Issue 4 (29th January 2016) - Ayub, Seemi; Gadji, Macoura; Krabchi, Kada; Côté, Sylvie; Gekas, Jean; Maranda, Bruno; Drouin, Régen
Abstract : Partial monosomy of the long arm of chromosome 7 has been characterized by wide phenotypic manifestations, but holoprosencephaly (HPE) and sacral agenesis have frequently been associated with this chromosomal deletion. A clear relationship between genotype and phenotype remains to be defined in the 7q deletion syndrome. Three patients (1, 2, and 3) were investigated with 7q terminal deletion and compared with similar deletion cases in the literature in order to stratify the phenotypes associated with 7q35 and 7q36 terminal deletion patients. Patients 1, 2, and 3 were carrying a de novo terminal deletion at bands 7q36.2, 7q35, and 7q36.1, respectively. In patient 3, a small Xq28 duplication was also identified by array‐CGH. Our patients presented with heterogeneous phenotypic manifestations, which could imply the possible role of environmental factors (multifactorial inheritance), structural variations in the non‐coding regions, penetrance, and/or polymorphism. The varying length of deletion was also taken into account. Growth retardation was the most frequent symptom found in both 7q35 and 7q36 patients we reviewed. The occurrence of HPE and sacral malformation together was seen in less than 10% of the reviewed cases in both kinds of deletion. HPE was associated mainly in cases with an unbalanced translocation. © 2016 Wiley Periodicals, Inc.